Need Help(IIT Problem)

Q - If \(f(x) = \displaystyle\int_1^x \dfrac{\ln t}{1 + t} \text{dt}\) where \(x > 0\) ,
Then the value of x satisfying the equation f(x)+f(1x)=2 f(x) + f\left(\dfrac{1}{x}\right) = 2 is

I attacked the question in this way,
f(x)+f(1x)=2 f(x) + f\left(\dfrac{1}{x}\right) = 2
Differentiating both sides with respect to x.
f(x)+f(1x)1x2=0...1 f'(x) + f'\left(\dfrac{1}{x}\right)\cdot \dfrac{-1}{x^2} = 0 \quad \quad ...1

Applying leibniz theorem in the given integral,
f(x)=lnx1+xf(1x)=ln(1x)1+1x=xlnx1+x f'(x) = \dfrac{\ln x}{1+x} \quad \quad f'\left(\dfrac{1}{x}\right) = \cfrac{\ln\left(\frac{1}{x}\right)}{1 + \frac{1}{x}} = \dfrac{-x \ln x}{1 + x}
Substituting values of f(x) and f(1x)f(x) \ and \ f'\left(\dfrac{1}{x}\right) in equation 1 ,

lnx1+x=xlnx1+x \dfrac{\ln x}{1+x} = \dfrac{x \ln x}{1 + x}
x=1\boxed{x = 1}
x = 1 is the wrong answer.Can you please help me out where i am wrong?

#Calculus #Integration #Function #IITJEE

Note by Akhil Bansal
5 years, 8 months ago

No vote yet
1 vote

  Easy Math Editor

This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.

When posting on Brilliant:

  • Use the emojis to react to an explanation, whether you're congratulating a job well done , or just really confused .
  • Ask specific questions about the challenge or the steps in somebody's explanation. Well-posed questions can add a lot to the discussion, but posting "I don't understand!" doesn't help anyone.
  • Try to contribute something new to the discussion, whether it is an extension, generalization or other idea related to the challenge.
  • Stay on topic — we're all here to learn more about math and science, not to hear about your favorite get-rich-quick scheme or current world events.

MarkdownAppears as
*italics* or _italics_ italics
**bold** or __bold__ bold

- bulleted
- list

  • bulleted
  • list

1. numbered
2. list

  1. numbered
  2. list
Note: you must add a full line of space before and after lists for them to show up correctly
paragraph 1

paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)example link
> This is a quote
This is a quote
    # I indented these lines
    # 4 spaces, and now they show
    # up as a code block.

    print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
MathAppears as
Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.
2 \times 3 2×3 2 \times 3
2^{34} 234 2^{34}
a_{i-1} ai1 a_{i-1}
\frac{2}{3} 23 \frac{2}{3}
\sqrt{2} 2 \sqrt{2}
\sum_{i=1}^3 i=13 \sum_{i=1}^3
\sin \theta sinθ \sin \theta
\boxed{123} 123 \boxed{123}

Comments

The error in your method is that you differentiated both sides of a non-identical equation. Only functions (implicit or explicit) and identities can be differentiated (this is one of the basic rules of differentiation).

The statement f(x)+f(1/x)=2f(x)+f(1/x)=2 is an equation in terms of xx which holds true for a finite set of values of xx, i.e., the equality here is non-identical. As such, you can't differentiate it w.r.t xx.

The answers on this post highlights the fallacy of differentiating an equation which is not an identity.

Prasun Biswas - 5 years, 8 months ago

Log in to reply

Thanks both of you.

Akhil Bansal - 5 years, 8 months ago

I think that you first need to look at the function g(x)=f(x)+f(1x)g(x) = f(x) + f\left(\dfrac{1}{x}\right) in general.

Then g(x)=f(x)+f(1x)1x2=ln(x)1+x+ln(x)x(1+x)=xlnx+ln(x)x(1+x)=ln(x)x.g'(x) = f'(x) + f'\left(\dfrac{1}{x}\right)*\dfrac{-1}{x^{2}} = \dfrac{\ln(x)}{1 + x} + \dfrac{\ln(x)}{x(1 + x)} = \dfrac{x\ln{x} + \ln(x)}{x(1 + x)} = \dfrac{\ln(x)}{x}.

Integrate using the substitution u=ln(x)u = \ln(x) to find that g(x)=12(ln(x))2+C.g(x) = \dfrac{1}{2}(\ln(x))^{2} + C.

Next, since g(1)=0g(1) = 0 we see that C=0,C = 0, and so g(x)=12(ln(x))2.g(x) = \dfrac{1}{2}(\ln(x))^{2}.

Finally, for this to equal 22 we need to have (ln(x))2=4ln(x)=±2,(\ln(x))^{2} = 4 \Longrightarrow \ln(x) = \pm 2,

and so either x=e2x = e^{2} or x=1e2.x = \dfrac{1}{e^{2}}.

Brian Charlesworth - 5 years, 8 months ago

Log in to reply

I really liked your solution,great observation that g(1)=0g(1) = 0 .Thanks!

Akhil Bansal - 5 years, 8 months ago

I am getting x=e2x=e^2

Tanishq Varshney - 5 years, 8 months ago

Log in to reply

Correct answer is e2e^2 and e2 e^{-2}

Akhil Bansal - 5 years, 8 months ago

akhil i am connected brillant now

Kunal Garg - 5 years, 7 months ago

Log in to reply

Good,sabse pehle mje apna phone number de..

Akhil Bansal - 5 years, 7 months ago

Log in to reply

are you subscribed to brilliant

Kunal Garg - 5 years, 7 months ago

Log in to reply

@Kunal Garg No

Akhil Bansal - 5 years, 7 months ago
×

Problem Loading...

Note Loading...

Set Loading...